Legislative Balances Needed Between Environment and Agriculture - Esther Muñiz Espada (New Medit)

(untitled)
The pressure and the excess of environmental obligations of the European legislation on agriculture has ended up affecting the original purposes of agriculture and agri-foodstuffs, therefore, art. 39 of the TFEU. The time has therefore come to consider at the legislative level what should be the correct balance between the environment and agriculture or productivity. Agriculture, food and the environment are an inseparable equation. Bureaucracy and certain environmental obligations affect the profitability of the agricultural sector.